HUBUNGAN PENGETAHUAN DENGAN STATUS KEBERSIHAN GIGI DAN MULUT PADA PENDERITA DIABETES MELITUS DI PUSKESMAS RAWANG JAMBI - Berliana Sari; Idham Halid; Pahrur Razi (Jurnal Kesehatan Gigi, 2017)
TITLEThe relationship of knowledge and oral hygiene status in diabetes mellitus patients in Puskesmas Rawang jambiABSTRACTDiabetes Mellitus disease produces manifestations in the oral cavity including saliva, tongue, gingival mucosa, periodontal tissue and teeth. To achieve the target achievement of dental services in 2010, various programs have been done, either promotive, preventive, curative, or rehabilitative. The purpose of this research is to know the correlation of knowledge with dental and oral hygiene status at diabetes mellitus patient at Puskesmas Rawang Jambi.This research use analytic survey method, sampling with total sampling method of all type II diabetes mellitus patient at PuskesmasRawang Jambi with 40 respondents. The analysis used univariate and bivariate analysis (chi-square test).The results showed that the knowledge of diabetes mellitus in Puskesmas Rawang Jambi from 40 people, the majority with medium criteria is 70%, and high criteria is only 22.5% and dental and oral hygiene status is more bad criteria 82,5%, and good criteria only 5%. Bivariate analysis using Chi-square test was known to not have knowledge relation with dental and oral hygiene status, where p-value = 0,569. It is suggested to increase promotive and preventive efforts in people with diabetes mellitus at Puskesmas Rawang Jambi. Keywords : Knowledge, dental and mouth hygiene status